2011
DOI: 10.1021/es200827t
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Various Sludge Digestion Conditions on Sulfonamide, Macrolide, and Tetracycline Resistance Genes and Class I Integrons

Abstract: Wastewater treatment processes are of growing interest as a potential means to limit the dissemination of antibiotic resistance. This study examines the response of nine representative antibiotic resistance genes (ARGs) encoding resistance to sulfonamide (sulI, sulII), erythromycin (erm(B), erm(F)), and tetracycline (tet(O), tet(W), tet(C), tet(G), tet(X)) to various laboratory-scale sludge digestion processes. The class I integron gene (intI1) was also monitored as an indicator of horizontal gene transfer pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
209
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 366 publications
(235 citation statements)
references
References 26 publications
24
209
2
Order By: Relevance
“…2). The BES anode essentially functioned as an anaerobic digester under the open circuit condition, but the log removal of ARGs achieved (ranging from 2.16 to 3.19 log reduction) here was higher than that reported for mesophilic and thermophilic anaerobic digesters (Ma et al, 2011). This higher removal could be related to the highly specific environment (acetate as the sole carbon source) and limited electron acceptors in the BES anode (no electron acceptors were added in the substrate).…”
Section: Fate Of Antibiotic Resistant E Coli and Args Under The Mfc contrasting
confidence: 66%
See 3 more Smart Citations
“…2). The BES anode essentially functioned as an anaerobic digester under the open circuit condition, but the log removal of ARGs achieved (ranging from 2.16 to 3.19 log reduction) here was higher than that reported for mesophilic and thermophilic anaerobic digesters (Ma et al, 2011). This higher removal could be related to the highly specific environment (acetate as the sole carbon source) and limited electron acceptors in the BES anode (no electron acceptors were added in the substrate).…”
Section: Fate Of Antibiotic Resistant E Coli and Args Under The Mfc contrasting
confidence: 66%
“…The culture isolated with HiCrome™ m-TEC agar was confirmed to be E. coli by detecting the E. coli specific gene uidA (Maheux et al, 2009). A series of PCR assays served to detect ARGs (Ma et al, 2011). The presence of sulI, tet(E) and intI1 was confirmed to be of the expected size using gel electrophoresis (SI Fig.…”
Section: Molecular Analysesmentioning
confidence: 98%
See 2 more Smart Citations
“…In this study, it was found that intI1 gene had significantly positive correlation with sulI, sulII, tetA, tetC, tetG, and tetBP genes, indicating that intI1 gene may play certain role in the dissemination of ARGs. Previous study have demonstrated that integrons can be used by Gram-positive and Gram-negative bacteria to stockpile and express different exogenous resistance genes and are considered to play a central role in the worldwide problem of antibiotic resistance [39][40][41]. Partridge et al found that sulI gene was carried within the 3 conserved region of class 1 integron, and such an association may facilitate and enhance its persistence [42].…”
Section: Discussionmentioning
confidence: 99%